PEMANFAATAN MIKROKONTROLER AT89S51 SEBAGAI PENGGESER FASA PADA ANTENA ARRAY - Rikki Vitria (Elektron : Jurnal Ilmiah, 2012)
Utilization of microcontroller especially MCS-51 family has been widely implemented in various applications, such as control and telecommunications applications. One of them is the phase shifting array antenna in the telecommunication field. The Array Antenna was designed from some of dipole antenna. Each element at dipole antenna has a different phase and can be controlled electronically. The phase shifting was done using AT89S51 microcontroller that functioned as an electronic switch on the transmission cable connection. The phase of the array antenna will be moved without moving the structure of the array antenna itself, so that the direction of radiation pattern can be changed in accordance with the phase shifting between the antenna elements.